Study to evaluate association of umbilical coiling index and perinatal outcome - Chholak, Deepika; Gupta, Pratiksha; Khajotia, Santosh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To correlate the perinatal outcome by noting the umbilical coiling index. Methods: The umbilical cords of the babies born to 500 women, who delivered either vaginally or by lower segment caesarean section, were examined and umbilical coiling index was calculated. Results: There was significant correlation (p value 0.003) between. Hypercoiling (UCI >90th percentile) is associated with IUGR. Hypocoiling (UCI <10th percentile) is associated with: - Meconium staining liquor, high LSCS rates, low Apgar score <7 at 1 min and at 5 min respectively and NICU admissions of babies. Conclusions: Hypercoiling (UCI >90th percentile) is associated with IUGR Hypocoiling (UCI <10th percentile) is associated with meconium staining liquor, high LSCS rates, low Apgar score <7 at 1 min and at 5 min respectively and NICU admissions of babies.